The Harmonization of Wasathiyatul Islam: Transforming Values of Religious Moderation in the Dialectics of Indonesian Society - Tamam, Asep Majidi; Supardi, Adi; Erihadiana, Mohamad; Mardani, Dadan (International Journal of Islamic Educational Research, 2026)
The relationship between religious doctrine and national identity remains a critical discourse in the Muslim world. The object of this research is Wasathiyatul Islam (Islamic Moderation) in Indonesia, which serves as a theological framework for balancing religious observance with social justice. However, the emergence of rigid transnational ideologies poses a significant challenge to this harmony, creating a potential disconnect between religious doctrine and local culture. To address this issue, this research aims to analyze how the values of Wasathiyatul Islam are transformed and harmonized within the dialectics of Indonesian society. The study employs a descriptive qualitative method with a phenomenological approach. Data were collected through literature reviews and social observations, then analyzed using an interactive model to interpret the "lived experience" of moderation. The results reveal that the harmonization process is manifested through four key indicators: national commitment, tolerance, anti-violence, and accommodation of local culture. A synthesis of these findings demonstrates that moderation in Indonesia is not merely a top-down state policy but an organic, bottom-up cultural practice where local wisdom serves as a vessel for religious values. In conclusion, Wasathiyatul Islam successfully functions as a unifying instrument, creating a "State of Consensus" where Indonesian Muslims practice their faith devoutly while maintaining unwavering loyalty to the nation.